From Tailgating to Twitter: Fans' Use of Social Media at a Gridiron Matchup Between Two Historically Black Colleges - Carrie Brown; Erin Willis; Cody Havard; Richard L. Irwin (Journal of Applied Sports Management, 2015)
The current study investigated the uses and gratifications of attendees using social media at the Southern Heritage Classic (SHC), a Historically Black Colleges and Universities football game between Tennessee State University and Jackson State University. Descriptive data revealed how attendees used various types of media to find information about the SHC, and how social media was utilized by participants during and surrounding the event. Further, following Clavio (2011), two one-way ANOVAs found that attendees did not differ in their use of social media by sex, but did differ by age groups. Specifically, younger age groups were more likely than older attendees to utilize social media to gather information about the SHC. Theoretical implications are discussed, recommendations for practitioners are presented, and areas for future research identified.
Keywords: Social media; Fan behavior; Event Engagement